External and internal stability in set optimization. (3rd April 2019) - Karuna,; Lalitha, C. S.
Abstract: The main aim of this paper is to establish stability in set optimization in terms of convergence of a sequence of solution sets of perturbed set optimization problems to the solution set of the original set optimization problem both in the image space and the given space. The perturbed problems are obtained by perturbing the feasible set without changing the objective map. Formulations of external stability and internal stability are considered in the image space. External stability, which pertains to complete convergence of a subsequence of weak minimal solution sets, both in the sense of Hausdorff andKuratowski − Painlev e ´ convergence of sets, is established under certain compactness and continuity assumptions. This leads to the upperKuratowski − Painlev e ´ convergence of the sequence of solution sets in the given space. Internal stability is established for minimal solution sets under certain continuity, compactness and domination assumptions which leads to the lowerKuratowski- Painlev e ´ convergence of the sequence of solution sets in the given space. External stability for minimal solution sets and internal stability for weak minimal solution sets are deduced under the strict quasiconvexity assumption. In particular, the results are also deduced for a vector optimization problem.